Macrobenthos of Subtidal Habitat in Sematan Coastal Water, Sarawak - Fatimah A’tirah, Mohamad; Tasha Amira, Kamasahairuddin; Hazeeqah Filzah, Kassim (UNIMAS Publisher, 2024)
Community of macrobenthos in coastal area of Sematan, Sarawak is described from a dataset collected in August 2018. This study investigated the composition, density and diversity of subtidal macrobenthos in the coastal zones between Sematan and Samunsam Wildlife Sanctuary. Duplicate of benthic sediment samples from each of the four selected stations were collected using Ekman grab sampler and sieved. The macrobenthos were then sorted and identified under a stereomicroscope. Results showed that Polychaeta was the dominant taxa (84%), followed by Mollusca (12%) and Crustacea (4%). The density, diversity, richness and evenness index values fluctuated along the stations. Future studies focusing on the potential factors that might influence the distribution pattern of macrobenthos in Sematan coastal water could reveal the interaction among macrobenthos community and their environment.